Increasing Competency in Entering and Processing Accounting Data Using Spreadsheets for Education Personnel: Peningkatan Kompetensi Mengentri dan Mengolah Data Akuntansi Menggunakan Spreadsheet Bagi Tenaga Kependidikan - Oktaviani, Ayu Aulia; Dewi, Risa Nurmala; Wongso, Erni Suhartini; Lestari, Aulia Dwi; Santoso, Indah Kumalasari (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
The increasingly rapid development of Information Technology demands an increase in human resource capabilities and mastery of information technology. One of the computer programs that helps manage data is a spreadsheet application. As the demands of the world of work increase, especially in higher education, employees and educational staff need to make efforts to provide the best service. Therefore, efforts are needed to increase competency and skills effectively through training activities on the operation of number processing or spreadsheet applications for employees or educational staff at universities. The target of the activity is higher education education staff in Indonesia. This activity aims to increase participants' competency in entering and processing accounting data using spreadsheets. Improving computer accounting skills can support participant performance so that they can encourage the progress of their agency. To help partners solve the problem of increasing competence in accounting data entry and processing, counseling and training methods are used which include providing material, questions and answers, and practice using spreadsheets in data entry and processing accounting data.